HUBUNGAN PENGETAHUAN DENGAN TINGKAT KECEMASAN PADA KLIEN PRE OPERASI KATARAK DI BALAI KESEHATAN MATA MASYARAKAT (BKMM) MANADO - Rolly Rondonuwu; Lucia Moningka; Ramandha Patani (POLTEKKES KEMENKES MANADO, 2014)
Cataracts are opacities in the lens or loss of transparency of the lens resulting in a decrease in visual acuity. Which may occur as a result of hydration (fluid replenishment) lens, lens protein denaturation, or both, someone who had a cataract becomes hazy or blurred vision. One treatment of cataracts is surgery or surgery that often cause anxiety. One of the measures to reduce the level of anxiety is to prepare mentally from the patient. This research is analytic survey with cross-sectional approach, namely the relationship of knowledge to the level of anxiety in the client pre cataract surgery. This study aimed to determine the relationship of knowledge to the level of anxiety in the client pre cataract surgery. This research was conducted in Community Eye Health Center on 09 June to June 23, 2014 with a population of 75 people and the sample in this study amounted to 42 respondents. How to sampling by means of accidental sampling by using a list of questions (questionnaire). Research results with chi-square test assay values obtained α of 0.001 is smaller than α = 0.05. This shows that there is a significant relationship between knowledge with clients preoperative anxiety levels cataract, conclusion of this study is found that respondents who do not have anxiety with both existing Knowledgeable 2 (4.8%), respondents who have mild anxiety with knowledge well there are 15 persons (35.7%), respondents who have moderate anxiety with good knowledge there are 10 persons (23.8%), it can be concluded health education can reduce anxiety and increase knowledge in the preoperative cataract patients. This study nursing profession is expected to provide input for the nursing profession in developing an understanding of the client overcome anxiety preoperative cataract